EKSTRAK ETIL ASETAT DAN ETANOL DAUN SIRIH (Piper bette T.) DAPAT MEMPER.PENDEK WAKTU PERDARAHAN MENCIT (Mus Musculus) - Regina Tedjasulaksana (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Folk medicine made from herbal have many benefits for health and using in Indonesia for long time period. As traditional medicine, betel leaves have a benefit to stop epistaxis. Tannin is one of the secondary metabolite found in betel leaves extraxt, known to be effective material to stop bleeding. The purpose of this study is to know that ethyl acetate extract and ethanol extract of betel leaves can make shorter bleeding time in mice. This was an experimental study with completely randomized post test only control group design.This study was using four groups of mice as samples consist of six mice per group. Bleeding time was determined by bleeding tail method. This study found that mean value of bleeding time of negative control is 511.16 ± 83.90 second ; mean value of bleeding time of positive control is 271.66 ± 60.30 second;  mean value of bleeding time of ethyl acetate extract of betel leaves is 249.00 ± 39.14 second and mean value of bleeding time of ethanol extract of betel leaves is 283.66 ± 38.91 second.  Data analyzed with One Way Anova and this analyzed shown that there is a significant difference of bleeding time between negative control group and positive control group , ethyl acetate extract  and ethanol extract of betel leaves. The conclusion is ethyl acetate extract and ethanol extract of betel leaves can make shorter bleeding time in mice. And advanced study need to do to know the minimal concentration of these extracts to give maximal benefit as haemostatic.